Mixed methods study on the use of and attitudes towards safety checklists in interventional radiology. Issue 1 (10th June 2017) - Munn, Zachary; Giles, Kristy; Aromataris, Edoardo; Deakin, Anita; Schultz, Timothy; Mandel, Catherine; Peters, Micah DJ; Maddern, Guy; Pearson, Alan; Runciman, William
Abstract: Introduction: The use of safety checklists in interventional radiology is an intervention aimed at reducing mortality and morbidity. Currently there is little known about their practical use in Australian radiology departments. The primary aim of this mixed methods study was to evaluate how safety checklists (SC) are used and completed in radiology departments within Australian hospitals, and attitudes towards their use as described by Australian radiologists. Methods: A mixed methods approach employing both quantitative and qualitative techniques was used for this study. Direct observations of checklist use during radiological procedures were performed to determine compliance. Medical records were also audited to investigate whether there was any discrepancy between practice (actual care measured by direct observation) and documentation (documented care measured by an audit of records). A focus group with Australian radiologists was conducted to determine attitudes towards the use of checklists. Results: Among the four participating radiology departments, overall observed mean completion of the components of the checklist was 38%. The checklist items most commonly observed to be addressed by the operating theatre staff as noted during observations were correct patient (80%) and procedure (60%). Findings from the direct observations conflicted with the medical record audit, where there was a higher percentage of completion (64% completion) in comparison to the 38% observed. The focus group participants spoke of barriers to the use of checklists, including the culture of radiology departments. Conclusion: This is the first study of safety checklist use in radiology within Australia. Overall completion was low across the sites included in this study. Compliance data collected from observations differed markedly from reported compliance in medical records. There remain significant barriers to the proper use of safety checklists in Australian radiology departments.